2017
DOI: 10.1017/s1479262117000259
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation, Heritability estimates and GXE effects on yield traits of Mesoamerican common bean (Phaseolus vulgaris L) germplasm in Uganda

Abstract: Germplasm of common beans from the Mesoamerican gene pool races: Durango, Jalisco, Mesoamerica and Guatemala have highest genetic variation for the crop's improvement. The objective was to assign 50 common bean germplasm in Uganda into its gene pool races based on analyses of population structure. Secondly, to estimate heritability and effects of genotype × environment (GXE) interaction on common bean agronomic and yield traits in space and time. Sample genomic DNA was amplified in 2011 with 22 Simple sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…G × E interaction was not significant for days to emergence, days to first flower, plant height, pods per plant, pods weight, primary branches, root length, and 100-seed weight, implying that selections made in one environment can be usefully exploited in the other environments, which can expedite the process of cultivar development and cut the costs associated with this activity. Genotypic variations and G × E effects observed in this work were found in agreement with previous works [32,[35][36][37][38].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…G × E interaction was not significant for days to emergence, days to first flower, plant height, pods per plant, pods weight, primary branches, root length, and 100-seed weight, implying that selections made in one environment can be usefully exploited in the other environments, which can expedite the process of cultivar development and cut the costs associated with this activity. Genotypic variations and G × E effects observed in this work were found in agreement with previous works [32,[35][36][37][38].…”
Section: Discussionsupporting
confidence: 93%
“…Analysis of variance (ANOVA) for most of studied traits reflected that genotypic variances were highly significant within as well as across the environment, revealing their higher level of heritability. The findings of this study are in line with previous studies [38,41,42] stating that days to maturity, pods per plant, number of seeds per plant, and 100 seeds weight are less influenced by environmental forces and are highly heritable traits under multi-year/locations.…”
Section: Discussionsupporting
confidence: 92%
“…With the current advances in molecular markers, a number of studies have been conducted to assess genetic diversity, population structure, and genome-wide association in the common bean. A wide range of molecular markers, including restriction fragment length polymorphisms (RFLPs; Velasquez and Gepts, 1994;Freyre et al, 1998), random amplified polymorphic DNA (RAPD; Beebe et al, 2000;Durán et al, 2005), inter simple sequence repeats (ISSRs; González et al, 2005;Dagnew et al, 2014), amplified fragment length polymorphisms (AFLPs; Beebe et al, 2001;Papa and Gepts, 2003), simple sequence repeats (SSRs; Blair et al, 2007Blair et al, , 2009Blair et al, , 2010aAsfaw et al, 2009;Kwak and Gepts, 2009;Burle et al, 2010;McClean et al, 2012;De La Fuente et al, 2013;Mercati et al, 2013;Okii et al, 2014Okii et al, , 2017Gioia et al, 2019;Pereira et al, 2019), and single nucleotide polymorphisms (SNPs; Cortés et al, 2011;Blair et al, 2013;Goretti et al, 2013;Cichy et al, 2015a;Rodriguez et al, 2016;Lobaton et al, 2018;Raatz et al, 2019), have been used in common bean.…”
Section: Population Structure and Genome-wide Association Analysis Ofmentioning
confidence: 99%
“…This implies that markers are effective in identifying and transferring of resistance genes to susceptible commercial varieties in early generations. Pyramiding genes for disease resistance in a genotype is a more durable and sustainable strategy to control diseases, as multiple coinfections of pathogens are common in production fields and have been reported to substantially affect productivity of the common bean (Singh, 2001;Valentini et al, 2017;Okii et al, 2018). While developing inter-gene pool multipleparent genotypes, Okii et al (2017) showed the effectiveness of marker-assisted selection to pyramid genes of resistance as well as improve the agronomic qualities.…”
Section: Discussionmentioning
confidence: 99%